2007
DOI: 10.1017/s0022215107000047
|View full text |Cite
|
Sign up to set email alerts
|

Sternotomy for substernal goitre: an otolaryngologist's perspective

Abstract: Radiological evidence of extension of a substernal goitre to the aortic knuckle, or loss of tissue planes on computed tomography, should raise suspicion that the patient may require sternotomy for safe delivery of the gland. The otolaryngologist should plan surgery for these patients in a specialist centre, with the help of a thoracic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…9 Burns et al performed a sternotomy in only 3/140 patients with SSG, since, in their opinion, the more significant factors contributing to the need to perform sternotomy are CT evidence of adherence to the surrounding mediastinal tissues and extension of the goiter to, or below, the aortic arch. 25 White et al , based on a systematic review of the literature, suggested that sternotomy is more likely to be performed in the presence of a primary substernal goiter or a mass larger than the thoracic inlet. 11 Ahmed et al used extension beyond the aortic knuckle on chest X-ray as their landmark for the depth of substernal extension.…”
Section: Discussionmentioning
confidence: 99%
“…9 Burns et al performed a sternotomy in only 3/140 patients with SSG, since, in their opinion, the more significant factors contributing to the need to perform sternotomy are CT evidence of adherence to the surrounding mediastinal tissues and extension of the goiter to, or below, the aortic arch. 25 White et al , based on a systematic review of the literature, suggested that sternotomy is more likely to be performed in the presence of a primary substernal goiter or a mass larger than the thoracic inlet. 11 Ahmed et al used extension beyond the aortic knuckle on chest X-ray as their landmark for the depth of substernal extension.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggested that the need of sternotomy is defined as more likely to be performed as follows: (1) RG with >70% of the mass extending in the mediastinum [25], (2) goiters > 10 cm, history of previous thyroidectomy, presence of invasive carcinoma and ectopic goiter [26], (3) extension to or below the aortic arch [27], (4) presence of malignancy, localization of the posterior mediastinum, extension below the aortic arch, presence of ectopic goiter [28], (5) extension to or below the tracheae carina, increased weight of the thyroid [18].…”
Section: Discussionmentioning
confidence: 99%
“…23 patients (54.7%) showed with a significant symptomatology while 19 cases (45.3%) were asymptomatic and was accidently discovered. The mean neoplasms size was 9.97 cm in the benign group & 11.1 cm for the malignant group [18]- [20].…”
Section: Discussionmentioning
confidence: 92%